Detection and genotyping of enteroviruses in cerebrospinal fluid in patients in Victoria, Australia, 2007–2013. Issue 9 (29th January 2014) - Papadakis, Georgina; Chibo, Doris; Druce, Julian; Catton, Michael; Birch, Chris
<x xml:space="preserve">Abstract</x> Genotyping by VP1 fragment polymerase chain reaction (PCR) and nucleic acid sequencing to detect enterovirus (EV) genotypes was performed directly on 729 EV PCR positive cerebrospinal fluid (CSF) samples collected between 2007 and 2012 from Victorian hospital inpatients. The overall genotype identification rate from CSF‐positive material was 43%. The four most common genotypes identified were Echovirus 6 (24%), Echovirus 30 (17%), Echovirus 25 (10%), and Coxsackievirus A9 (10%), together comprising 61% of all EVs typed. The seasonal distribution of all EVs identified followed the recognized pattern of mainly summer epidemics. Three of the four predominant genotypes were present in each of the 6 years in which the study was conducted, with 20 other EV genotypes also detected, often in only a single year. Genotyping of EVs directly in CSF is faster, simpler and more sensitive than traditional virus neutralization assays performed on EV positive samples. J. Med. Virol. 86:1609–1613, 2014. © 2014 Wiley Periodicals, Inc.